A Square Deal for All: Historical Essays on Labour in Brandon - Black, Errol; Mitchell, Tom (Canadian Committee on Labour History, 2000)
The authors' careful analyses of labour and working-class organizations in Brandon [Manitoba] are aimed at reconstructing and disclosing aspects of the history of class and class relations. While other western Canadian cities, Winnipeg, for example, have received much deserved attention by historians, studies of other cities, such as Brandon, in the early 20th century help to provide a more well-rounded understanding of working-class life in Canada during this period. In the tradition of the new labour history Black and Mitchell pay close attention to the unique development of class relations in the community of Brandon, while placing that community in a broader, national context. This work includes a careful consideration of the working class in Brandon, the particular obstacles and challenges workers there faced, and makes an important contribution to our understanding of class relations in Canada. –Publisher's description
https://archive.org/details/squaredealforall0000blac OCLC: 45140483
Keywords: History; Labor; Labor Manitoba Brandon History; Labor movement; Labor movement Manitoba Brandon History; Manitoba Brandon; Mouvement ouvrier Manitoba Brandon Histoire; Travail Manitoba Brandon Histoire; Travailleurs Manitoba Brandon Histoire; Working class; Working class Manitoba Brandon History